(untitled) (Medical Forum Monthly, 2024)
Objective: This study investigates the impact of recurrent UTIs on CKD outcomes and evaluates various management strategies. Study Design: A prospective, observational, cross-sectional study. Place and Duration of Study: This study was conducted at the Department of Urology, at Bacha Khan Medical College & Mardan Medical Complex Mardan from July 2023 to June 2024. Methods: A total of 245 CKD patients were enrolled, with a mean age of 65.4 ± 10.2 years. Demographic and clinical data, including CKD stage, comorbidities, and UTI history, were collected. The number of UTI episodes, causative organisms, antibiotic resistance patterns, and management outcomes were also analyzed. Results: Recurrent UTIs were present in 61.2% of patients. Those with recurrent UTIs showed significantly faster eGFR decline (4.8 ± 1.2 vs. 2.1 ± 1.0 mL/min/year, p < 0.001) and increased serum creatinine levels (1.1 ± 0.5 vs. 0.5 ± 0.3 mg/dL, p < 0.001) compared to those without recurrent UTIs. Furthermore, recurrent UTI patients had higher rates of progression to ESRD (33.3% vs. 15.8%, p = 0.002), dialysis need (26.7% vs. 10.5%, p = 0.005), and mortality (16.7% vs. 8.4%, p = 0.03). The most common causative organism was Escherichia coli (65.3%), and 24.5% of bacterial strains were ESBL-producing. Management strategies, including empirical and targeted antibiotic use, showed varied success rates, with targeted therapy being most effective (88.2% improvement). Conclusion: Recurrent UTIs significantly worsen CKD progression and increase the risk of adverse outcomes. Effective management, particularly targeted antibiotic therapy, is crucial for improving patient outcomes in this high-risk population.